Advances in civil engineering and building materials : selected, peer reviewed papers from 2012 2nd International Conference on Civil Engineering and Building Materials (CEBM 2012), 17-18 November, Hong Kong /: selected, peer reviewed papers from 2012 2nd International Conference on Civil Engineering and Building Materials (CEBM 2012), 17-18 November, Hong Kong. (©2013) - Unknown
No abstract available